Transformasi digital UMKM: Analisis implikasi kinerja melalui adopsi teknologi berbasis TOE framework - Setiyawan, Ayu; Fanani, Galih Pramuja Inngam; Ramadhan, Novia Fajar (Nur Science Institute, 2025)
This study aims to analyze the extent of technology adoption and digital transformation, and how technological, organizational, and environmental factors influence the performance implications for MSMEs. This study employs a mixed-methods approach, combining qualitative and quantitative analyses using the Technology-Organization-Environment (TOE) framework, and is analyzed using JASP software, involving 100 MSME actors as respondents. The findings indicate that, among the examined factors, the environmental factor has the greatest influence on MSME performance. Meanwhile, technology adoption, although highly perceived by respondents, does not show a statistically significant partial effect. These findings affirm that various factors influence the success of digital transformation and that the level of technology adoption does not solely determine it. Organizational and environmental readiness also play a crucial role in supporting successful digitalization. This research provides important implications for developing strategic MSME digitalization policies. Enhancing MSME performance through digitalization can generate multiplier effects that contribute to public welfare, national competitiveness, and the expansion of job opportunities in the digital economy era.